Imperial triumph the Roman world from Hadrian to Constantine - Kulikowski, Michael (The Profile history of the ancient world, 2016)
This is a history of the Roman Empire from the 2nd to the mid-4th centuries. The main focus is on Emperors, would-be Emperors, and their families.